Supporting dyslexic adults in higher education and the workplace - Brunswick, Nicola, 1970-; Wiley InterScience (Online service) (Malden, MA : Wiley-Blackwell, 2012)
"Supporting Dyslexic Adults provides practical advice in supporting dyslexic adults in education and employment, and guidance on the latest research Provides an important overview of current research and practice in supporting dyslexic adults in education and employment, deftly combining academic understanding with everyday issues Contributors possess a wealth of practical experience in the field which provides an indispensible guide to the subject Case studies are included to capture the immediate experiences of dyslexic adults in education and at work to highlight prevalent issues Offers practical advice to adults with dyslexia, from how to disclose their particular needs to employers and colleagues to legal aspects of dyslexia support Highlights to employers the particular skills and strengths that dyslexic adults can bring to the workplace"--Provided by publisher.
"Supporting Dyslexic Adults provides an overview of the latest research and best practice in supporting adults with dyslexia in higher education and employment"--Provided by publisher.
Front Matter -- Dyslexia in UK Higher Education and Employment: An Introduction and Overview / Nicola Brunswick -- Section 1: Supporting Dyslexic Adults in Higher Education. Sociob6(BEmotional Aspects of Dyslexia / Ruth Gwernan-Jones -- How well are Students with Specific Learning Difficulties Prepared for Higher Education? A Case Study of a Pre- 1992 University / Vikki Anderson, Sue Onens -- Screening for Specific Learning Difficulties in Higher Education / Sarah Nichols -- The Complex Nature of Dyslexia Support in the Context of Widening Participation / Vivien Fraser -- Why can't i Learn? Metacognitive Strategy Instruction / Geraldine Price -- Supporting Higher Education Students who are Dyslexic / David Pollak -- Dyslexia Support at the Royal College of Art / Qona Rankin -- Dyslexia, eLearning and eSkills / E A Draffan -- Reading Comprehension in Adult Students with Dyslexia / Rob Fidler, John Everatt -- Dyslexia Support at University and on Work Placement / Pauline Sumner -- Preparing for Work / Fiona White, Richard Mendez, Rosanne Rieley -- Section 2: Supporting Dyslexic Adults in the Workplace. Disclosing Dyslexia / Alan Martin, David McLoughlin -- Self-Disclosure in Adults with Learning Disabilities and Dyslexia / Paul J Gerber, Lynda A Price -- Dyslexia on the Defensive / Sylvia Moody -- Achieving Success in the Workplace / Carol Leather, Bernadette Kirwan -- The Knowledge and Skills Required by a Specialist Tutor within the Field of Adult Support / Margaret Malpas -- Dyslexia and Disability Discrimination / John Mackenzie -- The Design and Development of the Sylexiad Typeface / Robert Hillier -- Dyslexia and Creativity / Morag Kiziewicz -- Index.s
Includes index.
Includes bibliographical references and index.
Print version record.
Keywords: Dyslexics -- Education (Higher) -- Great Britain; Dyslexics -- Employment -- Great Britain; Dyslexia -- Great Britain; EDUCATION -- Special Education -- Learning Disabilities; EDUCATION -- Special Education -- Communicative Disorders; Electronic books